Palaeoenvironment, palaeoclimate and age of the Brassington Formation (Miocene) of Derbyshire, UK - Matthew J. Pound; James B. Riding (2016)
The Brassington Formation is the most extensive Miocene sedimentary succession onshore in the UK. Because of its unique position at the margin of NW Europe, the pollen from this lithostratigraphical unit provides evidence on the development of vegetation affected by North Atlantic currents and hypothesized atmospheric circulation changes during the Middle to Late Miocene climate cooling. Palynostratigraphy suggests that the uppermost Kenslow Member of the Brassington Formation is not coeval. Previously, all occurrences of the Kenslow Member were assumed to be contemporary. The oldest pollen assemblage is from the more southern Bees Nest Pit, which represents a subtropical conifer-dominated forest of late Serravallian age ( c . 12 Ma). A younger assemblage was observed from the more northern Kenslow Top Pit; this indicates that a subtropical mixed forest was present during the early Tortonian (11.6–9 Ma). The shift from a conifer-dominated to a mixed forest was related to precipitation. Although the total precipitation did not change between the two assemblages, the younger assemblage had more uniform rainfall throughout the year. The diachronous nature of the Kenslow Member means that the depositional model of the Brassington Formation needs revising, and this will have implications for Neogene to recent uplift of the southern Pennines.